LITERATURE STUDY: THE DIFFERENCE IN RISK OF FALLS BEFORE AND AFTER CHAIR-BASED EXERCISE ON ELDERLY - Pita, Meicyana N; Sari, Chrisdina P; Muliono, Ari C (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Indonesian Ministry of Health Research stated that in 2017 the population of the elderly reached 23.66 million people (9.03%) and also predicted that it will continue to increase. The aging process causes declined physical capacity and mental, which makes the elderly have a higher risk of falls. One of the preventions of falls in the elderly is physical exercise to increase muscle strength and joint mobility. Chair-based Exercise is a physical exercise done by sitting, consisting of aerobic and muscle resistance exercise with Thera Band.Purpose: To analyze the risk of falls in the elderly before and after Chair Based Exercise.Method: This study used literature synthesis. Keywords collected the Articles due to the topic in the research proposal.Result: 13 articles were reviewed in this study. Most articles have similarities in research design, analysis techniques, sample characteristics, total sample, duration of the intervention, and effect of the intervention studied. The differences mainly on the age of the sample and the intervention method. The similarities between the articles and research proposal mostly on sample characteristics and measuring the risk of falls. The difference mostly in a total of the sample, research design, analysis technique, duration and method of the intervention.Conclusion: Only a few articles published Chair Based Exercise as an intervention method. There are similarities in the interventions given in the form of combination training, and it was found that the risk of falls was improved in the elderly. Therefore, research on the effect of Chair Based Exercise on the risk of falls in the elderly needs to be realized by enriching various inputs from literature studies.